2012
DOI: 10.1371/journal.pone.0032112
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Adenosine-Activated Chloride Transport by Ethanol in Airway Epithelia

Abstract: Alcohol abuse is associated with increased lung infections. Molecular understanding of the underlying mechanisms is not complete. Airway epithelial ion transport regulates the homeostasis of airway surface liquid, essential for airway mucosal immunity and lung host defense. Here, air-liquid interface cultures of Calu-3 epithelial cells were basolaterally exposed to physiologically relevant concentrations of ethanol (0, 25, 50 and 100 mM) for 24 hours and adenosine-stimulated ion transport was measured by Ussin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…For example, studies in individuals who harbor partially functional CFTR mutations demonstrate that CFTR abnormalities greatly increase the risk of recurrent idiopathic pancreatitis (34). Given that at least 15% of patients with idiopathic pancreatitis are heterozygous for CFTR mutations (3,35), and many causative CFTR mutations confer only modest dysfunction, it seems possible that CFTR dysfunction at the levels we observed is sufficient to increase the risk of both pulmonary and extrapulmonary disease, particularly when compounded by additional insults, such as alcohol, which has also been associated with CFTR dysfunction (36).…”
Section: Discussionmentioning
confidence: 73%
“…For example, studies in individuals who harbor partially functional CFTR mutations demonstrate that CFTR abnormalities greatly increase the risk of recurrent idiopathic pancreatitis (34). Given that at least 15% of patients with idiopathic pancreatitis are heterozygous for CFTR mutations (3,35), and many causative CFTR mutations confer only modest dysfunction, it seems possible that CFTR dysfunction at the levels we observed is sufficient to increase the risk of both pulmonary and extrapulmonary disease, particularly when compounded by additional insults, such as alcohol, which has also been associated with CFTR dysfunction (36).…”
Section: Discussionmentioning
confidence: 73%
“…26 In addition, Raju et al demonstrated that basolateral ethanol exposure (0, 25, 50 and 100 mM) for 24 hours reduced epithelial short-circuit currents (I SC ) in a dose-dependent manner. 27 …”
Section: Discussionmentioning
confidence: 99%
“…There is no standard in vitro model of the alveolar epithelial barrier to study drug transport, pharmacokinetics and bioreactivity; for example many in vitro studies utilise the A549 adenocarcinoma cell line as a substitute for primary human alveolar epithelial type II cells [ 24 26 ], whilst others utilise the Calu-3 human bronchial epithelial cell line, also derived from a pulmonary adenocarcinoma, to investigate changes in barrier function of large airway epithelium [ 27 , 28 ]. We believe it is also relevant to use cell lines derived from normal lung cells and primary cells [ 21 ].…”
Section: Introductionmentioning
confidence: 99%